2022
DOI: 10.1038/s41537-022-00306-z
|View full text |Cite
|
Sign up to set email alerts
|

Deconstructing heterogeneity in schizophrenia through language: a semi-automated linguistic analysis and data-driven clustering approach

Abstract: Previous works highlighted the relevance of automated language analysis for predicting diagnosis in schizophrenia, but a deeper language-based data-driven investigation of the clinical heterogeneity through the illness course has been generally neglected. Here we used a semiautomated multidimensional linguistic analysis innovatively combined with a machine-driven clustering technique to characterize the speech of 67 individuals with schizophrenia. Clusters were then compared for psychopathological, cognitive, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 82 publications
0
15
0
Order By: Relevance
“…Past NLP research has shown that inclusion of other characteristics of patients’ speech can improve predictive value of coherence models ( 15 , 17 , 18 , 27 , 35 ) – for instance, syntactic features, referential ambiguities, neologisms, cohesion scores, perseverations, and acoustic features. Since different patterns of linguistic impairment appear to be associated with different levels of psychopathology and functioning ( 44 ), future studies should consider developing and validating speech models of NAP containing more features of speech than coherence. Psychometric evaluation of coherence scores should also examine reliability, e.g., by intra-individual correlation of coherence scores across multiple measurement time points.…”
Section: Discussionmentioning
confidence: 99%
“…Past NLP research has shown that inclusion of other characteristics of patients’ speech can improve predictive value of coherence models ( 15 , 17 , 18 , 27 , 35 ) – for instance, syntactic features, referential ambiguities, neologisms, cohesion scores, perseverations, and acoustic features. Since different patterns of linguistic impairment appear to be associated with different levels of psychopathology and functioning ( 44 ), future studies should consider developing and validating speech models of NAP containing more features of speech than coherence. Psychometric evaluation of coherence scores should also examine reliability, e.g., by intra-individual correlation of coherence scores across multiple measurement time points.…”
Section: Discussionmentioning
confidence: 99%
“…Participants involved in the validity arm, that is, participants assessed with both the APACS and the remotely administered APACS Brief tests, underwent the first session (T0) in-person to comply with the standardized procedure of the APACS test, with all the precautions to reduce potential risks due to the COVID-19 pandemic (e.g., wearing an FFP2 mask, distancing at least 1 meter from participants, etc.). In-person sessions were audio-recorded, in line with previous uses of the APACS test (e.g., Bambini, Frau, et al, 2022).…”
Section: Design and Proceduresmentioning
confidence: 99%
“…As an additional limitation, the array of tools for pragmatic assessment is strikingly poor from the point of view of remote administration. Neuropsychological practice has started to move from traditional in-person paper-and-pencil examination towards more technological solutions, which include remote interaction between affected individuals and practitioners (Zanin et al, 2022), as well as assessment via automated methods (Bambini, Frau, et al, 2022;Gagliardi et al, 2021). The COVID-19 pandemic prompted a rapid increase in the use of tele-evaluation, no longer limited to specific contexts such as large countries covering huge areas, but extending to more routinized situations to continue providing services to patients from their homes, without the added risks such as for instance virus exposure (Marra et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The literature widely describes patients' "thought disorders, " including poverty of speech, disorganization in the discourse, which is hard to follow, derailment and tangentiality with a loosening of associations (Bleuler, 1950;Andreasen, 1986;DSM, 2013). The impairments lead to difficulties in interpersonal communication for patients (Elvevåg et al, 2010) and damage pragmatic abilities, contributing to social dysfunction (Bowie and Harvey, 2008); moreover, it is possible to underline correlations between types of schizophrenic pathology and linguistic functioning (Bambini et al, 2022), the damage of which is associated with a reduced brain specialization (Cavelti et al, 2018;Boer et al, 2020). These phenomena depict an overall monotony in schizophrenic speech (Dovetto et al, 2015;Cresti and Moneglia, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…To assess the psychopathology of schizophrenia, numerous evaluation scales have been employed since the 1960s. 1 However, it has become evident that these scales rely on human judgment, necessitating fresh approaches or analyses to interpret the symptomatic heterogeneity of the disease accurately (Bambini et al, 2022), characterized by variations from one individual to another and within the same individual at different disease stages.…”
Section: Introductionmentioning
confidence: 99%